Characterization of multidirectional carbon-nanotube-yarn/bismaleimide laminates under tensile loading - Vondrasek, Britannia; Evers, Cecil; Jolowsky, Claire; Odegard, Gregory M.; Zhiyong Liang; Czabaj, Michael (Composites. Part B, Engineering, 2024)
Unidirectional, cross-ply, and quasi-isotropic composite laminates are made from continuous carbon nanotube (CNT) yarns with bismaleimide (BMI) resin. The laminates are highly graphitic and have low resin content. Elastic modulus and strength of CNT/BMI laminates and IM7/8552 carbon-epoxy laminates are measured using a scaled-down tensile test method. For CNT/BMI laminates, the variation in the measured tensile modulus is high and the laminates fail in a more gradual manner than IM7/8552 laminates. Microscopy of the failed specimens indicates that intra-yarn splitting is a common feature in all CNT/BMI laminates tested. The results of this investigation will inform the development of CNT yarn reinforced composites for structural applications. [Display omitted] •Unidirectional, cross-ply, and quasi-isotropic laminates are tested in tension.•A small-scale tensile testing method is developed to measure laminate properties.•IM7 carbon fiber and CNT yarn reinforced laminates are both tested.•CNT yarn laminates fail more gradually than IM7 laminates.•Intra-yarn splitting is a common feature of failed CNT yarn laminates.